Remote service technology perception and its impact on customer-provider relationships : An empirical exploratory study in a b-to-b-setting - Paluch, Stefanie (Gabler Verlag, 2012)
Remote services represent a young, but already important and fast growing form of technology-mediated services,. Stefanie Paluch employs multiple qualitative methods to explore the perception of remote services and its impact on customer-provider relationships in USA, Germany and Sweden. She develops a comprehensive model about customers' holistic remote service experience and derives theoretical propositions that reflect main influence factors. Based on the empirical data, she generates managerial implications for remote service providers on how to increase the technology adoption and reinforce the relationships with their customers in high-technology environments.